Political economy of food system reform - Resnick, Danielle (Nature Publishing Group, 2020)
Policy packaging offers citizens better scope for assessing trade-offs in policy attributes and policymakers the opportunity to make unpopular reforms, including those needed to achieve healthy and sustainable food system transformation, more palatable to their constituents.